Pictures and Progress Early Photography and the Making of African American Identity - Smith, Shawn Michelle; Wallace, Maurice O. (Duke University Press, 2012)
Pictures and Progress explores how, during the nineteenth century and the early twentieth, prominent African American intellectuals and activists understood photography's power to shape perceptions about race and employed the new medium in their quest for social and political justice. They sought both to counter widely circulating racist imagery and to use self-representation as a means of empowerment. In this collection of essays, scholars from various disciplines consider figures including Frederick Douglass, Sojourner Truth, Ida B. Wells, Paul Laurence Dunbar, and W. E. B. Du Bois as important and innovative theorists and practitioners of photography. In addition, brief interpretive essays, or "snapshots," highlight and analyze the work of four early African American photographers. Featuring more than seventy images, Pictures and Progress brings to light the wide-ranging practices of early African American photography, as well as the effects of photography on racialized thinking.Contributors. Michael A. Chaney, Cheryl Finley, P. Gabrielle Foreman, Ginger Hill, Leigh Raiford, Augusta Rohrbach, Ray Sapirstein, Suzanne N. Schneider, Shawn Michelle Smith, Laura Wexler, Maurice O. Wallace